PENGARUH KEPEMIMPINAN,KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT.XYZ - Chairizal, Zulfahmi .; Djamil, Masydzulhak . (Indikator: Jurnal Ilmiah Manajemen & Bisnis, 2019)
Abstract Management company especially often confronted with a problem work employee who low satisfaction , it can be seen on high level employees his the issuance, various ways in doing management in order to make employee take comfort in their work , because it will be an undesired effect a less well if the employee get out often gave way to a new , which results in the company performance. Research aims to understand the influence of, compensation , leadership and workplace employees of PT.XYZ central jakarta work with satisfaction. Data collection in for causing the questionnaire to all employees of PT.XYZ covering 35, employees and by using spss 25,With the results of the testing of hypotheses indicates that there is a difference between positive and significant compensation, leadership and workplace employees work with satisfaction, simultaneously and in a third, variable compensation , leadership and workplace all have had a positive impact and significant for employees work with satisfaction